Perceptions of Islamic Religious Education Teachers on the Child Protection Act and the Teacher Law at MTs Nahdlatul Ulama Maron Probolinggo - Izzul Illah; Fathullah Rusly; Imam Muttaqin (CV. Rayyan Dwi Bharata, 2023)
Education will give a child's character and personality which is carried to adulthood. Implementation of education can be used with various methods where one of them is the method of giving rewards (award) and punishment (punishment). However, the imposition of this punishment is now often used as a debate among the community because some people think that the imposition of punishment violates children's rights. The child protection law, which was supposed to function to protect children, has become a weapon that can undermine the teacher's role and duties as an educator. It is appropriate that there is a convergence of the punishment method in education and child protection laws so that teachers can still carry out their educational roles and tasks properly without feeling intimidated by the applicable laws. The purpose of this study is to provide an overview of the convergence of punishment methods in education and child protection laws. The method used is a qualitative method with a literature review and comparative study approach. The results of the research show that both teachers and students actually have a legal umbrella that regulates the rights and obligations of each. However, regulations that protect teachers are still considered blunt and have not been able to provide full protection for teachers. Therefore, it is necessary to converge the punishment method in education and child protection laws so that teachers do not bear the bad consequences of disciplining students by giving punishment.